(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The objective was to increase the bioavailability of quercetin by creating a controlled release formulation using nanosponges based on cyclodextrin. A 3-factor, 3-level Box-Behnken design with quercetin was loaded into nanosponges using the freeze-drying process based on the early testing. The prepared nanosponges were examined after being described and made into tablets. The quercetin-loaded nanosponges have particle sizes ranging from 36.45 to 135.27 nm, encapsulation efficiencies ranging from 42.37 to 88.44%, and drug release percentages at 6 hours ranging from 53.04 to 82.64%. The Quercetin interaction with nanosponges was validated by the FTIR, DSC, and XRD investigations. The medicine released from the nanosponges buccal tablets in vitro at a rate of 99.75 percent, and stability testing showed no significant changes within six months after the nanosponges were transformed into tablets. In-vivo studies in rats showed that quercetin optimised nanosponges tablets Cmax of 6.27±0.06 ng/ml was significantly higher (p<0.05) than the pure drug's Cmax of 3.07±0.086 ng /ml. Both the nanosponges tablet formulation and the pure drug suspension had Tmax values of 4.0±0.07 and 0.5±0.08 h, respectively. The nanosponges tablet formulation had a greater AUC0-infinity(38.54±0.65 ng.h/ml) than the pure drug suspension formulation 7.84±1.08 ng.h/ml. In comparison to the pure drug, the nanosponges tablet formulation had a considerably greater AUC0-t (p<0.05). Poorly soluble Quercetin tablets developed for regulated drug delivery shown enhanced complexing ability with increased bioavailability using cyclodextrin-based nanosponges.